Early assessment of left atrial function after cardioversion predicts recurrence of atrial fibrillation. (8th February 2021) - Kupczynska, K; Michalski, BW; Trzos, E; Miskowiec, D; Szyda, L; Siedlecki, P; Wierzbowska-Drabik, K; Lipiec, P; Kasprzak, JD
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The restoration of sinus rhythm (SR) improves the mechanical function of the heart. Purpose: To assess left atrial (LA) function before and within 24 hours after successful electrical cardioversion (EC) and its prognostic value for atrial fibrillation (AF) recurrence during 24 months follow-up. Methods: Prospective study involved 71 patients with non-valvular AF (mean age 64 ± 13 years, 61% male). All patients underwent echocardiography before and after EC. We analysed standard parameters in two-dimensional echo, pulse-wave Doppler and tissue Doppler echocardiography. Using speckle-tracking method we assessed peak atrial longitudinal strain (PALS) and peak atrial contraction strain (PACS). Results: During follow-up we noticed AF recurrence in 48 (68%) patients. Median time to AF recurrence was 2.4 (IQR 1 to 6.9) months. Left ventricular ejection fraction as well as E/E' and PALS assessed during AF were statistically insignificant as potential predictors in univariate regression model. Receiver operating characteristic curve analysis revealed that left atrial volume index >37 ml/m² (AUC = 0.811, p < 0.0001), E/A ratio >2.1 (AUC = 0.828, p < 0.0001), A wave ≤0.4 m/s (AUC = 0.662, p = 0.01), mean E/E' ratio during sinus rhythm >8.5 (AUC = 0.815, p < 0.0001), mean A' wave of ≤5.5 cm/s (AUC = 0.848, p < 0.0001), PALS-SR ≤14.1% (AUC = 0.767, p < 0.0001), PACS ≤4.3% (AUC = 0.883, p < 0.0001) were the optimal cut-off values for predicting AF recurrence. Conclusions: The assessment of LA and diastolic function conducted within 24 hours after successful cardioversion predicts long-term maintenance of sinus rhythm.